Prevalence of Substance Use and Associated Factors Among High School Adolescents in Rithepani, Lekhnath-2, kaski, Nepal - Gurung, A; Shrestha, N; Silwal, M; Gurung, R; Ojha, S (Journal of Gandaki Medical College-Nepal, 2017)
Background: Substance use is a major public health concern in global settings, and is very common during adolescence period leading to physical and/or mental health complications. This study assessed the prevalence of substance use and associated factors among high school adolescents in Rithepani 2, Lekhnath, Kaski, 2073. Objectives: The study was designed to provide estimates of substance use by school-going adolescents in Lekhnath and to identify risk factors associated with. Methods: A school based cross-sectional study was conducted from 17th October to 21st October, 2016 among eighth to 12th grade high school students in the Rithepani-2, Lekhnath. Participants were selected by purposive sampling techniques, and data were collected using questionnaire. Frequency, percentage, means, SD and chi-square test was performed to identify factors associated with substance use. Results: Majority of the respondents 93 (56.4%) belonged to the age group 15 - 18 years. Majority of the respondents 88 (53.3%) were males and 50 (30.3%) were studying in grade 11. Majority of the respondents 140 (84.8%) were Hindus and 104 (63%) of the respondents belonged to upper caste group. In terms of education of the respondents’ parents, majority of the respondents’ mothers 68 (41.2%) had completed their secondary education and similarly, majority of the respondents’ fathers 78 (47.3%) had completed their secondary education. Majority of the respondents’ mothers 129 (78.2%) were housewives and majority of the respondents' fathers 48 (29.1%) were businessmen. Majority of the respondents 136 (82.5%) belonged to nuclear family and 93 (56.4%) had per month family income more than Rs 15,000. Among 165 respondents prevalence of substance use was found to be 10 (6%). Regarding the associated factors majority of the respondents 162 (98.2%) had good relation with their parents, 101 (61.2%) respondents’ family members do not use substance, 128 (77.6%) respondents reported that substance use was not accepted in their culture. the prevalence of substance use by the respondents is 6.1% in which five (50%) respondents consume alcohol, eight (80%) take cigarette, one (10%) use tobacco and two (20%) take ganja. Among the substance users, four (40%) reported imitating parents and four (40%) reported curiosity as the cause for them to initiate substance use. Regarding the accessibility of the substances among the respondents who use substances, three (30%) respondents said that it’s very difficult whereas one (10%) said that it’s very easy for them to have access to the substances. Majority of the respondents who use substances 6 (60%) avail the substance/s from their friends. Regarding the Association, there is a significant association between prevalence of substance and substance use by family members with the χ2 value of 7.61 and p-value 0.006 which is less than 0.05 significant level. There is also a significant association between the prevalence of substance use and its cultural acceptance with the χ2 value of 4.65 and p-value of 0.031 which is less than 0.05 significant level. There is a significant association between the prevalence of substance abuse and ethnicity with the χ2 value of 11.81and with the p-value 0.037 which is less than 0.05 significant level. Conclusions: The prevalence of substance use among high school adolescent students in selected higher secondary school was found to be 6.1%. There was significant association between prevalence of substances use and cultural acceptance of participants, ethnicity and use of substances by the family members. Based on the findings of the study researcher suggests to initiate awareness and co-ordination program between the school and parents. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 43-48